Предмет: Алгебра,
автор: 170799
Решить показательное уравнение
Приложения:
Ответы
Автор ответа:
0
2^(x^2) * 2^( - x/4) = 8^(1/4)
2^(x^2 - x/4) = 2^(3/4)
x^2 - x/4 = 3/4
4x^2 - x - 3 = 0
D = 1 + 48 = 49
x₁ = ( 1 + 7)/8 = 1;
x₂ = ( 1 - 7 )/8 = - 3/4
2^(x^2 - x/4) = 2^(3/4)
x^2 - x/4 = 3/4
4x^2 - x - 3 = 0
D = 1 + 48 = 49
x₁ = ( 1 + 7)/8 = 1;
x₂ = ( 1 - 7 )/8 = - 3/4
Похожие вопросы
Предмет: Физика,
автор: Аноним
Предмет: Биология,
автор: ObitoUchiiha
Предмет: Математика,
автор: ekettle
Предмет: История,
автор: dasha123092